A New Approach of BLDC Motor Using Fuzzy Fractional Order PID (International Journal of Innovative Research in Computer Science & Technology, 2022)
In order to manage the speed of brushless  DC (BLDC) motors, this research presents a novel hybrid  control method that simultaneously regulates the DC bus  voltage of the inverter and the BLDC motor reference  current. A fractional-order PID (FOPID) controller  manages the BLDC motor reference current, and a fuzzy  logic controller manages the inverter DC bus voltage. A  modified harmony search (HS) metaheuristic technique is  developed for adjusting the FOPID controller parameters.  Three separate working scenarios—no load, varying load,  and varying speed—are used to test the motor's  capabilities. Run the proposed controller at a high speed to  verify its efficacy. The suggested hybrid control method  has also been put to the test. weighed against FOPID and fuzzy-based speed control techniques The outcomes  demonstrate the effectiveness of the suggested control.  approach enables more accurate speed control over a wide  region.
Keywords: Approach; BLDC; Fractional